Desenvolvimento e avaliação de um ambiente virtual imersivo de treinamento para manutenção de bomba hidráulica - Muhlen, Luciano Silva Martins Von (2025)
This study presents the development and evaluation of an immersive virtual environment designed for tasks at the training center of an agricultural machinery and implements company. This Virtual Reality application simulates real-world training, maintenance, and understanding tasks related to the operation of hydraulic pumps and motors, built using resources from Blender and Unity tools, supported for the Meta Quest 3 device. After the implementation of the solution, we executed a pilot study with 23 volunteer participants to preliminarily evaluate the usability and user experience using the System Usability Scale, User Experience Questionnaire, and open-ended questionnaire. The usability results showed a mean score of 90 points, suggesting that most users had a positive, efficient, and satisfactory experience during the interaction process. The user experience aspects (dependability, novelty, efficiency, attractiveness, perspicuity, and stimulation) also presented strongly positive evaluations, with mean values per aspect ranging from 2.22 to 2.78, considering a scale from-3 (extremely negative) to +3 (extremely positive). The qualitative content analysis corroborated the results of the objective questionnaires, revealing opportunities for improvement, such as graphical interface adjustments, inclusion of a basic tutorial, expansion of simulation scenarios, and integration of Augmented Reality resources. In this context, the solution proves to be an innovative tool for the training center, capable of simplifying the understanding of complex hydraulic components and promoting practical and interactive experiences, with more significant engagement and potential retention of the content.